Let’s do Engineering broadens young children’s understanding of engineers - Bridle, Helen; Rajendran, Gnanathusharan (Frontiers in Education, 2024)
This study developed and applied a new job card methodology to investigate what five-year-olds in Scotland understand in relation to engineers and engineering. Children were shown images of different jobs and asked to identify the jobs and select the cards showing engineers. The methodology was utilised pre and post intervention to determine whether an intervention combining engineer role model imagery and hands-on activities (specifically Let's Do Engineering) would successfully broaden perspectives of engineering, and whether there would be any differences between boys and girls in terms of the effectiveness of the intervention. Sixteen 5-6 year old children from one school participated and prior to the intervention could only correctly recognise an average of 1.5 engineers. Post-intervention, however, all children were able to successfully identify multiple engineers within the job cards, achieving in excess of a three-fold increase in the number of engineers correctly identified, even at two months after the end of the intervention. When comparing data for boys and girls. analysis showed that there were no between group gender differences in either perceptions or in strength of impact of the intervention. The engineers identified were well-spread across the different engineering fields, indicating that the children developed a broad understanding of different engineering disciplines.